Enhanced radioresponse with a novel recombinant human endostatin protein via tumor vasculature remodeling: Experimental and clinical evidence - Meng, Mao-Bin; Jiang, Xiao-Dong; Deng, Lei; Na, Fei-Fei; He, Jia-Zhuo; Xue, Jian-Xin; Guo, Wen-Hao; Wen, Qing-Lian; Lan, Jie; Mo, Xian-Ming; Lang, Jin-Yi; Lu, You (Radiotherapy and oncology, 2013)
This study aimed to examine the effect of the novel recombinant human endostatin (rh-Endo) protein on tumor vasculature, and to explore and evaluate the optimal scheduling of rh-Endo and radiotherapy (RT). Tumor-perfusion parameters and hypoxia were monitored after rh-Endo treatment in 10 non-small cell lung-cancer (NSCLC) patients. Eight-week female C57BL/6J mice were randomized to receive rh-Endo or control (saline) once daily for 12days when Lewis lung carcinoma (LLC) reached approximately 100–150mm3. On planned days, tumors were measured for cell apoptosis, microvessel density, pericytes, blood-vessel morphology, and tumor hypoxia. The tumor response under different combinations of rh-Endo and RT schedules was evaluated. Tumor hypoxia was significantly reduced 5days after rh-Endo in NSCLC patients, and a similar result was found in the LLC mouse model. The anti-tumor effect was markedly enhanced when RT was administered within the remodeling period compared to any other treatment schedule. rh-Endo treatment remodeled the tumor vasculature after 5days by reducing microvessel density and increasing pericytic coverage of the vessel endothelium. This study demonstrated decreased hypoxia in animals and patients upon rh-Endo treatment, which also enhanced the radioresponse within the vasculature-remodeling period. The optimal clinical combination of rh-Endo and RT warrants further investigation.